Grounded theory as a qualitative research strategy - Kuchko, Elena E.; Vishniakova, Marharyta V. (Journal of the Belarusian State University. Sociology, 2023)
The specifics of using a sound theory strategy in the process of qualitative research are considered. The peculiarity of this method is reflected – the cyclical nature of the study. The stages of the strategy implementation are listed: collection of primary data, processing and preliminary analysis, data collection. The use of theoretical sampling in qualitative research is justified, the volume of which is determined by the saturation of the categories. The uniqueness of multi-stage processing of the obtained data is presented, the sequence of work of a sociologist during open, axial and selective coding is revealed. Tools are presented that allow you to structure research materials and visualise the emerging theory (analytical memos and diagrams). The types of analytical memos (coded, theoretical and operational notes) are presented. Rules for preparing analytical memos and diagrams are given that allow one to represent the logic of the researcher’s analytical thinking and the logic of theory formation based on the data obtained. Limitations of implementing a grounded theory strategy are indicated.